Metaphase chromosome structure is dynamically maintained by condensin I-directed DNA (de)catenation - Piskadlo, Ewa (2018)
This deposit is composed by the main article and the supplementary materials are present in the publisher's page in the following link: https://elifesciences.org/articles/26120/figures.